Patient perspective and satisfaction with different types of vascular access in hemodialysis: a systematic review and meta-analysis - Amirali Ahrabi; Sepideh Poshtdar; Javad Salimi; Mohammad Ashouri; Mehdi Yaseri (BMC Nephrology)
Abstract Background To assess satisfaction and perspectives of adult hemodialysis (HD) patients on different vascular access (VA) types (AVF, AVG, CVC) by synthesizing quantitative studies using validated questionnaires, focusing on overall satisfaction, physical symptoms, social functioning, and complications. Methods We systematically searched Medline, Web of Science, and Scopus for studies assessing adult HD patients’ perspectives on VA using structured questionnaires. Risk of bias was assessed using the Newcastle-Ottawa Scale. Meta-analysis was performed using a random-effects model across three pairwise comparisons: AVF vs. CVC, AVF vs. AVG, and CVC vs. AVG. Results Of 1,253 records, 11 studies (n = 2910) met inclusion criteria. AVF patients had higher overall satisfaction compared to those with CVCs (MD: 7.06%, 95% CI: 2.98–11.14). Compared to AVG, AVF patients had higher overall satisfaction, though not statistically significant (MD: 5.12%, 95% CI: − 0.42 to 10.66; p = 0.069). Dissatisfaction with physical symptoms was significantly higher in AVF patients than in those with CVCs (MD: 8.76%, 95% CI: 4.19 to 13.34). Compared to CVC, AVF patients reported significantly lower dissatisfaction in both social functioning (MD: − 9.48%, 95% CI: − 15.98 to − 2.98) and dialysis-related complications (MD: − 10.08%, 95% CI: -12.66 to -7.50). Conclusions AVFs are associated with higher overall patient satisfaction compared to other VA types. While AVF patients experience more physical discomfort, this is outweighed by significantly greater satisfaction in areas such as social functioning and dialysis-related complications. These findings emphasize the importance of considering patient-reported outcomes when evaluating VA options in HD care. Clinical trial number Not applicable.